Deep endometriosis transvaginal ultrasound in the workup of patients with signs and symptoms of endometriosis: a cost analysis. (18th September 2019) - Leonardi, M; Martin, E; Reid, S; Blanchette, G; Condous, G
Tweetable abstract: An endometriosis‐focused ultrasound may negate a two‐step surgery pathway, including diagnostic surgery, and save healthcare money. Abstract : Objective: Deep endometriosis transvaginal ultrasound (DE TVS) is accurate in the detection of ovarian endometriosis and DE; however, realisation of its full potential and utilisation remains variable. As such, patients may require a two‐step surgical approach (diagnostic followed by therapeutic laparoscopy) or experience incomplete surgical treatment. Besides the clinical implications, the economic impact of a two‐step approach to diagnosis and treatment on the healthcare system is likely to be significant. We aim to compare the economic costs of two diagnostic models of care for patients with potential endometriosis. Design: Cost analysis using Markov model with 12‐month time horizon comparing the economic costs of two diagnostic models. Setting: The study used a hypothetical population of 1000 women visiting a public tertiary gynaecology clinic. Population: Women with potential endometriosis. Estimates for endometriosis prevalence and severity were drawn from local Australian hospital data. Methods: The conventional model (M1) includes the basic TVS and diagnostic laparoscopy. The novel model (M2) includes the DE TVS. Probabilistic sensitivity analysis was conducted to capture the uncertainty in the information used to populate the models. Main outcome measure: Changes to government, health‐service and patient costs with the adoption of the DE TVS compared with standard diagnostic methods. Costs are given in Australian dollars (AU) and also in pound sterling (£). Results: The total annual cost of the novel model (M2) is AU12, 547, 724.03 (£6, 826, 673.63), cheaper than the conventional model (M1), which cost AU13, 472, 161.67 (£7, 329, 620.15). Conclusions: For a population of 1000 women, the integration of the DE TVS may save healthcare costs of AU924, 437 (£502, 946.17) annually. Tweetable abstract: An endometriosis‐focused ultrasound may negate a two‐step surgery pathway, including diagnostic surgery, and save healthcare money.